The Impact of Instructional Method on the Application of Kinesio Taping® Techniques for Occupational Therapy Students - Theresa Rice; Husny Amerih; Diane Brown (Journal of Occupational Therapy Education, 2017)
This research utilized a crossover study design to analyze the differences in learner satisfaction, confidence, and accuracy when comparing in-person, video, and written instructional methods. The study was conducted on a group of 32 occupational therapy students from a local university by teaching them two different Kinesio Taping® protocols. Satisfaction and confidence were measured by survey. The participants completed tapings, then were rated by an instructor to obtain accuracy data. The study found that learning satisfaction was rated higher following video instruction. Regarding confidence, there was a statistically significant difference in the level of confidence for students viewing video instruction for one of two taping techniques presented. No significant difference was found between groups in accuracy in taping after different instructional methods. The use of multiple instructional methods was reported as the most beneficial and preferred method in the study. This study highlights the potential benefits of utilizing multiple instructional methods to aid in student learning.